Experimental Study on the Dynamic Characteristics of a New Long-Short Pile Composite Foundation under Long-Term Train Load. (30th January 2023) - Zhu, Zhao-rong; Guan, Wei; Han, Kan; Wu, Hong-gang; Zhao, Shou-quan; Liu, Xu
Abstract : Long-short pile composite foundation (PC-LSPCF) composed of part-screw pile and cement-soil compaction pile is a new railway foundation treatment method, which has been widely used in high-speed railway construction projects in China. To explore the dynamic characteristics and deformation characteristics of railway PC-LSPCF under long-term train loads, the dynamic characteristics of long piles, short piles, and soil between piles under long-term train loads are tested by an indoor dynamic model test. The dynamic amplification of pile and soil under dynamic load and the temporal and spatial distribution of peak response are analyzed, and the stress and deformation development mechanism of PC-LSPCF under cyclic loading of large-cycle trains is revealed. The results show that the neutral point of the long pile is at 1/2 of the pile length and that of the short pile is at 3/8 of the pile length. The part-screw pile has a certain absorption effect on vibration energy. The deformation of a long-short pile composite foundation under long-term train loads can be divided into three stages: extreme growth, transition, and stability. The train speed is negatively correlated with the cumulative settlement of the long-short pile composite foundation. The higher the train speed, the smaller the cumulative settlement, and the smaller the number of cycles of the N-S curve entering the gentle period. As the number of train cyclic loads increases, the load-sharing relationship of the long pile-short pile-soil system will be redistributed. The research results have important reference significance for the optimization design of high-speed railway foundation treatment.